Sustainable Agriculture: Economic Aspects - Čiegis, Remigijus (Ekonomika, 2004)
Sustainable agriculture synthesizes a variety of concepts associated with agricultural practices and their socio-economic impacts. In this article, some-requirements, for the development of sustainable-agriculture in Lithuania are analysed within the ecological economics framework. First, sustainable agriculture is discussed within the context of environmental economics. After this more theoretical part, the Common Agricultural Policy reforms, trends of sustainable agriculture in EU and requirements for the development of sustainable agriculture in Lithuania are elaborated.